Analysis of polymorphic variants of the dopamine transporter (DAT1) gene polymorphism and personality traits among athletes - Michalowska-Sawczyn, M.; Lachowicz, M.; Grzywacz, A.; Suchanecka, A.; Chmielowiec, J.; Chmielowiec, K.; Chycki, J.; Trybek, G.; Zmijewski, P.; Cieszczyk, P. (Journal of Human Kinetics, 2020)
Personality traits, especially in sport are modulatory factors of athletes` behavior - his/ her conscientiousness, the will to achieve an aim, perseverance and motivation of activity. Not only are biological predispositions related to anatomical or biochemical traits of success, but they are also largely determined by personality traits that result from genetic factors. In our research we joined tests of athlete`s personality in correlation with genotypes of the dopamine transporter (DAT1) gene polymorphism. The selection of this polymorphism was based on previous reports connecting the influence of dopamine with motivation and numerous arguments supporting its correlation with human behavior. We observed significant differences among polymorphisms DAT 9/9, 9/10, 10/10 in terms of proportion of particular genotypes between athletes and the control group. We also found significant differences in the NEO FFI sten scale for conscientiousness. We noticed that anxiety was related with genotypic variants of DAT1, specifically the 9/10 VNTR variant, which conditioned lower levels of anxiety in the group of tested athletes. By contrast, the lower sten value of agreeability was statistically significant for the group of athletes that were carriers of the 10/10 VNTR genotype. Heterozygous 9/10 VNTR among athletes showed lower levels of anxiety in comparison with the control group, whereas agreeability determined using the NEO FFI scale represented a lower value among athletes that had the 10/10 polymorphism. We may thus conclude that the presence of polymorphic variants of the dopamine transporter gene corresponds to athletes` personality traits.